Larvicultura de tambaqui (Colossoma macropomum) em diferentes densidades no sistema de bioflocos - Silva, Nárcia Carolina Santos da (2021)
Due to the growing demand in quantity and quality of fish, the intensification of the production of tambaqui larvae and fry (Colossoma macropomum) requires the adoption of management techniques that increase density rates, without compromising animal health and well-being and reducing environmental impacts. In view of this scenario, a new technology has gained prominence in aquaculture worldwide, the cultivation of fish in a biofloc system (BFT). The use of biofloc technology allows cultivation with better water quality, making it possible to use high stocking densities, providing greater productivity when compared to conventional production systems. Despite the benefits found in this system, bioflocs are still not widespread in larvicultures, and there is a lack of technical and scientific information regarding the economic indicators related to the creation of tambaqui. Based on the assumption, the objective of this study was to evaluate the zootechnical performance and economic viability of tambaqui larvae submitted to different storage densities in a biofloc system. A total of 140,000 tambaqui post-larvae (initial weight of 0.00058 ± 0.00003g) were randomly distributed in 12 circular tanks of 15m³ during 65 days of cultivation and were subjected to the following treatments: T1 (clear water + 833 larvae / m³ ); T2: (BFT + 833 larvae / m³); T3 (BFT + 1,250 larvae / m³). The animals, in all treatments, were fed with commercial powdered feed (40% CP), ad libitum, six times a day (7:00 am, 9:00 am, 11:00 am, 1:00 pm, 3:00 pm and 5:00 pm). Biometrics were performed every 15 days and at the end of the 65 days of cultivation, the animals had an average weight of 4.55 ± 0.29g and 5.25 ± 0.28g, respectively for T2 and T3, total length 57.56 ± 1.15 mm in T2 treatment and 59.79 ± 0.96 mm in T3 treatment and body condition factor 0.77 ± 0.41 and 0.88 ± 0.43 for T2 and T3, respectively. The daily weight gain of T3 treatment fish (0.31 ± 0.026) was better compared to T2 (0.22 ± 0.024). The experimental design used was a completely randomized design, using three treatments and four repetitions (totaling 12 experimental units). To calculate the economic viability of the system, disbursements that occurred in production were taken into account, depreciation of items that include fixed capital, in addition, the remuneration or opportunity cost of the production factors employed were also evaluated, using the zootechnical indexes found. in T2 a total revenue of R $ 55,007.40 was found, proving to be sufficient to cover the total production costs, which was R $ 54,562.34, differently from the density of 1,250 larvae / m³ (T3), which proved to be economically not viable in tambaqui larviculture. At the end of the experimental period, it was found that the use of the biofloc system with a stocking density of 833 larvae / m³ provided favorable zootechnical indexes, with better survival rates in tambaqui larviculture in comparison to the other treatments, in addition to showing itself economically feasible when designed for small scale commercial larviculture.